Comparative pharmacokinetics of Ding‐Zhi‐Xiao‐Wan preparation and its single herbs in rats by using a putative multiple‐reaction monitoring UPLC‐MS/MS method. Issue 3 (7th September 2020) - Sun, Yufei; He, Yang; Liu, Shuxin; Gao, Hongxue; Pi, Zifeng; Song, Fengrui; Liu, Zhiqiang; Liu, Shu
Abstract: Introduction: The formula of Chinese medicine, Ding‐Zhi‐Xiao‐Wan (DZXW), has the distinct feature of compatibility therapy, which is attributed to the interactions of multi‐herbs. However, the quantification problem caused by the absence of pure reference standards is a bottleneck to clarify the compatibility advantages from the perspective of pharmacokinetics (PKs). Objective: This study aimed to develop a putative multiple‐reaction monitor (PMRM) strategy for exploring the comparative PKs of DZXW and its single herbs. Methods: First, precursor ion and tandem mass spectrometry (MS/MS) chromatograms were obtained via ultra‐high‐performance liquid chromatography coupled with quadrupole time‐of‐flight MS (UHPLC–Q‐TOF‐MS) under different collision energy (CE) values. Then, the two most abundance ions in the MS/MS chromatograms were chosen as product ions, and CE values were selected according to the abundance of the product ion peaks. Next, a PMRM strategy consisting of optimal MRM parameters was constructed. Finally, the established PMRM parameters were imported to UHPLC coupled with triple quadrupole MS (UHPLC–TQ‐MS) for quantification. Results: The strategy was exemplified by the comparative PK study of DZXW and its single herbs. This strategy could extend the PK scopes of multi‐components. The quantitative results displayed substantial variations in PK parameters between DZXW and its single herbs. Conclusion: The PK parameters indicated that the DZXW formula could increase the exposure levels of most ingredients and reduce the maximum concentration ( C max ) of Radix Polygala, indicating that herb compatibility could produce synergistic effects and diminish possible toxic effects. This study provides a viable orientation for the compatibility investigation of traditional Chinese medicine. Abstract : A novel putative multiple‐reaction monitor (PMRM) strategy whose MRM transitions and corresponding parameters were transformed from UHPLC–Q–TOF MS in MS/MS mode independent of standards, was developed. The PMRM strategy predicted parameter could be directly applied to MRM quantitation on UHPLC–TQ MS and achieved favorable performance for multi‐components quantification. This strategy was exemplified by investigating the comparative PK process of DZXW formula and its single herbs.